The Dynamics of Farmer Motivation in Cattle Breeding: A Case Study of Mario Marennu Cattle Group, Kulo District - Baharuddin, Dewi; Nugraha, Angga; Purnomo, Nurul (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2024)
Farmer motivation is critical in increasing the productivity and sustainability of livestock businesses, especially in rural areas. This study aims to identify the level of farmer motivation in Mario Village, Kuro District, and Sidenreng Rappang Regency and analyze the factors that influence it. With a quantitative descriptive approach and multiple regression analysis using SPSS 16.0 software, this study provides an in-depth description of the relationship between age, education, and livestock farming experience factors on farmer motivation locally. This study aimed to determine the level of farmer motivation in Mario Village, Kulo District, Sidenreng Rappang Regency, and the factors that influence this motivation. The method used was quantitative descriptive, and the sample consisted of 63 respondents. Data were collected through questionnaires and analyzed using multiple regression using SPSS 16.0 software. The results showed that two main factors significantly influenced farmer motivation: age and livestock farming experience. This can be seen from the regression coefficient of age (X1) reaching 0.500 and farming experience (X2) reaching 0.320. These values show a significant value of less than 0.05, indicating that they significantly influence farmer motivation